Cortical Thickness in Young Treatment-Naive Children With ADHD. (November 2015) - Yang, Xiao-Ru; Carrey, Normand; Bernier, Denise; MacMaster, Frank P.
Objective: This study aimed to investigate the cortical thickness in areas of the brain that are hypothesized to be involved in response inhibition and error-monitoring behaviors. The authors hypothesized that children with ADHD would have a thinner prefrontal cortex (PFC) and anterior cingulate cortex (ACC) than healthy children.Method: In all, 25 ADHD and 25 healthy control male children (5-12 years) underwent magnetic resonance imaging.Results: The authors found thinner right superior frontal gyrus in ADHD patients compared with controls ( t = 2.01, df = 45, p = .049). The older children with ADHD drove this effect when participants were further subdivided into a younger and older age group (older participants: p = .004; younger participants: p = ns ).Conclusion: These findings have implications for the developmental trajectory of the frontal lobe in ADHD.